Postcolonial world and postmodern identity: some implications for language teaching - Rajagopalan, Kanavillil (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper discusses some of the consequences of the new ways of thinking about identity. It is argued that identity, as conceived in terms of postmodernity, has a direct impact on language teaching, given that the very concept of language (just as much as that of the native speaker of a language) (both of which have traditionally been viewed in all-or-nothing terms) will need to be rethought.